Teachers’ Professional Competences in Self-Regulated Learning: An Approach to Integrate Teachers’ Competences as Self-Regulated Learners and as Agents of Self-Regulated Learning in a Holistic Manner - Karlen, Yves; Hertel, Silke; Hirt, Carmen Nadja (Frontiers in Education, 2020)
Competences in self-regulated learning (SRL) are important prerequisites for success in school and beyond. Teachers play a crucial role in students’ development of SRL. When focusing on teachers’ professional competences in SRL, their experiences as self-regulated learners and their competences as agents of SRL are important. At present, an integrative and holistic framework that combines these two important aspects of SRL with regard to teachers’ professional competences in SRL is absent. First, this paper introduces a theoretical framework for teachers’ professional competences and instructional practices in SRL that integrates teachers’ competences as self-regulated learners with their competences as agents of SRL. This integrative approach allows for differentiated analyses of particular aspects of competences and creates the possibility to deeply understand the reasons why teachers do or do not promote SRL in classrooms. In the second part of this paper, the interplay of teachers’ professional competences as self-regulated learners and agents of SRL, with their intention to implement SRL in classes and their self-reported SRL teaching practices, is examined using data provided by 106 in-service teachers from primary and secondary schools. We assessed teachers’ professional knowledge about SRL (i.e., content knowledge about SRL [CK-SRL] and pedagogical content knowledge about SRL [PCK-SRL]) with two different knowledge tests. Teachers’ beliefs (i.e., implicit theories about SRL and beliefs about promoting SRL) and their motivations (i.e., self-concept about one’s SRL and self-efficacy to promote SRL) were assessed with self-report measures. We found that teachers had small to average amounts of CK-SRL and PCK-SRL. Teachers reported positive beliefs about and motivation toward SRL. Most importantly, the results highlight the significance of differentiating between teachers’ competences as self-regulated learners and as agents of SRL when examining teachers’ implementation of SRL. The findings provide support for particular aspects of the integrative approach outlined in the theoretical framework and suggest that this approach can be the basis for further research exploring the interplay of teachers’ competences as self-regulated learners and as agents of SRL in more detail, particularly with regard to how aspects of teachers’ competences in SRL impact their SRL instruction in classes and students’ SRL development.